Assessment of interradicular spaces for miniscrew placement in class 1 subjects / Nagham Al-Jaf, Rohaya Megat Abdul Wahab and Mohamed Ibrahim Abu Hassan - Nagham Al-Jaf; Abdul Wahab, Rohaya Megat; Abu Hassan, Mohamed Ibrahim (Faculty of Dentistry, 2015)
Objectives: To assess interradicular spaces of maxilla and mandible in subjects with class I sagittal skeletal relationship as an aid for miniscrew placement. Materials and Methods: The study was carried out using cone-beam computed tomography (CBCT) images of 47 adult subjects with class I skeletal relationship. Interradicular spaces were obtained at the alveolar processes from first premolar to second molar at 2 different vertical levels (6 and 8mm) from the cementoenamel junction (C.E.J). Results: In the maxilla, the highest interradicular space existed between second premolar and first molar. In the mandible, the highest interradicular space existed between first and second molar. All mandibular measurements were higher than their respective maxillary measurement. Generally, availability of interradicular space increases apically in both arches, but the difference is not significant. In the maxilla, male subjects' measurement were significantly higher at 8 mm level between second premolar and first molar and between first and second molar Conclusions: Interradicular spaces in the maxillary and mandibular alveolar spaces are available for miniscrew placement. In both arches, a more apical location provides more interradicular space. However, careful planning is needed to avoid sinus perforation.